A Case Study On The Implementation Of E-Learning System At Multimedia University - Saad Sultan, Waleed Hassan (2004)
This study examines an evaluation of student's e-learning experience at Multimedia University during the 2004/05 academic year. The aim of this study is to provide an initial investigation of the MMLS programme and how the university can gain from the feed back of the respondents. These key evaluation and analysis, identified by interview with former students conducted from the university four faculties.